ANALISIS PENGARUH LIKUIDITAS DAN MARJIN KEUNTUNGAN TERHADAP PENDAPATAN BAGI HASIL MUSYARAKAH DENGAN SUKU BUNGA KONVENSIONAL SEBAGAI MODERASI - Fauzan, Muhammad Azmi; Mawardi, Wisnu (Faculty of Economics and Business Diponegoro University, 2016)
The global Islamic finance industry has demonstrated its ability to withstand the crisis for the values of the Islamic finance industry has prepared itself from speculations. On the other hand, there is support for the Indonesian government to develop sharia economic system since the majority of the Indonesian people embrace the religion of Islam. Islamic banking system, which prohibits a transaction of interest (riba/usury,) has become the investment solutions as well as the funding needs for both Muslims and non-Muslims. However, the community needs for banking products in accordance with sharia cannot be fulfilled properly because of Islamic banking has been made conventional interest rate as an indirect reference to determine the level of revenue sharing.This study analyzed the effect of liquidity associated with liquidity and the profit margin on revenue for the Bank’s results on transactions Musharaka financing moderated by JIBOR (Jakarta Interbank Offered) on Islamic Banks in Indonesia from 2010 to 2014. The sampling technique was purposive sampling method to 7 Islamic Banks which has total assets of more than 1 trillion rupiah. Secondary data were obtained from Bank Indonesia and web publications related bank. The analysis was Moderated Regression Analysis (MRA).The results of this study indicate that the liquidity and margins with a significant and positive direction results on transactions Musharaka financing, the interest rates JIBOR moderated with a negative but not significant relationship between the liquidity on transactions Musharaka financing, the interest rates JIBOR moderated with a positive and significant relationship between the margins on transactions Musharaka financing.